Redeeming grace ebook - Miller, Emma (Hannah's Daughters., 2012)
With nowhere to turn, penniless widow Grace Yoder travels with her young son to the Amish community of Seven Poplars. She hopes to reunite with the Plain father she never knew—and become part of the community. Though her father is deceased, his new family still welcomes her. Grace is overcome with gratitude. But when handsome family friend and Mennonite John Hartman offers her a job in his veterinarian office, Grace discovers a beautiful bridge between the two worlds. And prays John will ask her to stay by his side.